Integration of digitalization and green finance for sustainable and resilient manufacturing and service operations in China: an empirical analysis - Zhou, Xu; Sou, Katat; Gao, Ziting; Xiong, Jian (Frontiers in Environmental Science, 2025)
This paper integrates digitalization with green finance strategies to investigate their combined impact on carbon emissions and economic resilience in China’s manufacturing and service sectors, particularly within the context of achieving China’s 2030 carbon neutrality goals. Leveraging data from the China Emissions Accounts and Datasets (CEADS), a simultaneous equations model based on the Cobb–Douglas production function and the Environmental Kuznets Curve (EKC) is employed to quantify the effectiveness of green financial initiatives and digital transformation in carbon emission mitigation. The empirical results reveal substantial regional disparities, with digitalization significantly amplifying the effectiveness of green finance in the more economically and technologically advanced eastern regions, thereby enabling these areas to achieve carbon neutrality sooner compared to the central and western regions. This study highlights the pivotal role of digital technologies, such as artificial intelligence and blockchain, in enhancing transparency, efficiency, and scalability of green financial instruments, including carbon finance and green bonds. Policy recommendations underscore that targeted investments in digital infrastructure combined with robust green finance policies are essential for accelerating regional transitions toward carbon neutrality. The findings provide critical insights for policymakers and investors, not only in China but also globally, illustrating how synergistic digital-green financial frameworks can effectively support sustainable economic growth aligned with international climate objectives.